2021
DOI: 10.1093/her/cyab035
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of social distancing compliance in an Australian sample

Abstract: Pandemics are associated with high rates of morbidity and mortality, and the coronavirus disease (COVID-19) pandemic has been the most fatal coronavirus outbreak of the 21st century. To reduce person-to-person transmission, interventions such as social distancing have been recommended; however, it is anticipated that 80% compliance is required to control the outbreak. A questionnaire was used to assess the factors related to compliance with social distancing restrictions using a modified version of the Theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(53 reference statements)
0
3
1
Order By: Relevance
“…The ndings of the current study also showed that CPBs adoption increases along with mean BI scores in terms of preventing COVID- [35], which was inconsistent with the ndings of the current investigation. The inconsistency may be due to a disconnect between perception and reality, and population factors.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The ndings of the current study also showed that CPBs adoption increases along with mean BI scores in terms of preventing COVID- [35], which was inconsistent with the ndings of the current investigation. The inconsistency may be due to a disconnect between perception and reality, and population factors.…”
Section: Discussioncontrasting
confidence: 99%
“…distancing intention, and frequent hand washing in preventing the COVID-19, respectively[25,33,34]. SN was not a predictor of social distancing intention, according toThacker et al (2022) …”
mentioning
confidence: 83%
“…The perceived benefits of physical distancing can be enhanced by enhancing knowledge of physical distancing to reduce the spread of COVID-19. Among the general population in Australia, knowledge of the restrictions was reported to predict intention to adhere to physical distancing ( 42 ). Of course, we can consider that healthcare workers may better understand the benefits of physical distancing, and about 70% of participants were nursing professionals or medical doctors in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is critical for individuals to have the capacity to differentiate high- versus low-quality health information, obtain accurate information, process and understand information to develop behaviors that allow them to protect themselves and others against the virus. Indeed, Thacker et al [ 3 ] showed that people who knew and understood COVID-19-related restrictions were more likely to adhere to them. Consequently, the overarching goal is to promote citizens to modify everyday social interaction behaviors toward forming new daily habits of health prevention behaviors.…”
Section: Introductionmentioning
confidence: 99%